Indicadores para avaliação dos objetivos de desenvolvimento sustentável (ODS) em instituições de ensino superior (IES) - Griebeler, Juliane Sapper (2019)
In 2015, after the closure of the 8 Millennium Development Goals (MDGs), the 17 Sustainable Development Goals (SDG), inserted in Agenda 2030, were launched. The commitment on SDGs culminates in a global mobilization to reach goals in because they cause various actors to commit to the cause. In this context, Higher Education Institutions (HEIs) are one of the important agents in achieving the proposed goals. They serve as examples both through their actions on their campuses as well as in the dissemination of knowledge through teaching, research and extension activities. However, to assess their intensity of contribution to SDG, a performance evaluation by metrics is required. In this sense, indicators are presented as a useful tool in this process. Therefore, the present research aims at the elaboration of a set of indicators that will serve as instruments to monitor the evolution of SDG in the context of HEIs. This is a qualitative and quantitative study based on the technique of content analysis. The methodology consisted in the collection of indicators of sustainable development based on the existing bibliography. Afterwards, with the help of the software Nvivo 10, the indicators found were related with the SDGs. The relationship was based on the most frequent SDG's words found in the selected indicators. The results indicated an initial list with 432 indicators, of which 268 were selected because they had at least one of the keywords searched for. Thus, redundant indicators were excluded and, when necessary, indicators were aggregated, resulting in a final listing of 61 indicators that were ranked in order of importance through the perception of experts who contributed to the survey by answering a questionnaire sent to them. The research resulted in a set of 61 indicators that, in general, the experts consulted affirm that they are sufficient to evaluate the contribution of the HEI to the SDG, and that their HEIs will be able to collect the data to fulfill the indicators.